2019
DOI: 10.1177/2158244019853920
|View full text |Cite
|
Sign up to set email alerts
|

Attitudes Toward Different Types of Chinese-English Code-Switching

Abstract: This study investigates language attitudes held by Chinese-English bilinguals toward two types of switching to English in mandarin Chinese discourse, that is, intraclausal and interclausal switching. Participants with varying degrees of English proficiency were sampled from four cities in mainland China and one oversea city, London. A variation of matched-guise technique, open guise technique, was used to collect attitudinal responses toward code-switching. Quantitative analyses showed that the participants ge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 35 publications
0
3
0
1
Order By: Relevance
“…In other words, in Weibo users’ eyes, the linguistic resource of self-mockery is not a linguistic resource pertinent to everyone but is a privilege afforded to those with high social status and a great amount of achievements, that is, scholars and experts. ‘[W]hat is evaluated is not the language practice per se, but the social position embodied in the language practice and the identity aligned with such positions’ (Liu, 2021; see also Bi, 2011; Gao, 2022; Liu, 2019). It is a linguistic resource which is licensed to a certain group of individuals in association with the distribution of the power, which although is not officially stipulated, is commonly accepted in people’s understanding of the world.…”
Section: Findings and Analysismentioning
confidence: 99%
“…In other words, in Weibo users’ eyes, the linguistic resource of self-mockery is not a linguistic resource pertinent to everyone but is a privilege afforded to those with high social status and a great amount of achievements, that is, scholars and experts. ‘[W]hat is evaluated is not the language practice per se, but the social position embodied in the language practice and the identity aligned with such positions’ (Liu, 2021; see also Bi, 2011; Gao, 2022; Liu, 2019). It is a linguistic resource which is licensed to a certain group of individuals in association with the distribution of the power, which although is not officially stipulated, is commonly accepted in people’s understanding of the world.…”
Section: Findings and Analysismentioning
confidence: 99%
“…Past research on bilingual adults has demonstrated that code-switching is associated with several factors, which relate to various motivations, such as: motivations regarding the speakers executing the code-switch, which includes their perception of and attitudes to the language(s), the social environment surrounding the speakers, including the nuclear family, relationships and (sub-)communities; such as (ethnic) identity (Yim and Clément 2019), (different) inter-community constraints (Bhatt and Bolonyai 2011), and attitudes toward code-switching (Koch et al 2001). Additional motivations closely relate to social attitude and likability (Liu 2019), context (formal vs. informal setting) (Koch et al 2001; see also Schau et al 2007), and (ethnic) group identity (Auer 2005;De Fina 2007). In addition, adults may be motivated to code-switch by discourse-related factors, for example when trying to explain or clarify a certain concept (David 2003).…”
Section: Adult Code-switchingmentioning
confidence: 99%
“…Multilinguals often switch between their languages (Moodley 2007;Paradis and Nicoladis 2007;Song 2016), and young children are no exception: even children as young as two years have been found to switch between languages in a conversation (Comeau et al 2003;Lanvers 2001;Paugh 2005). Many studies have investigated adults' speech to shed more light on the motivations for code-switching (Bhatt and Bolonyai 2011;De Fina 2007;Koch et al 2001;Liu 2019;Yim and Clément 2019). This work has shown that switching between languages can be motivated by a variety of factors, and involve, amongst others, attempts to avoid breakdown in conversation or to better express a concept in one of the languages (David 2003;Du-Re 2012).…”
Section: Introductionmentioning
confidence: 99%
“…ตั วอย่ างที ่ ป็ อปแลค (Poplack, 1980: 583) (Campbell, 1963) 5) ทั ศนคติ เป็ นตั วน าให้ เกิ ดการกระท า กล่ าวคื อ ทั ศนคติ กั บพฤติ กรรมมี ความสั มพั นธ์ ซึ ่ งกั น และกั น นั กจิ ตวิ ทยาสั งคมบางกลุ ่ ม (Allport, 1935;Fishbein & Ajzen, 1974;Williams, 1974) เชื ่ อว่ าทั ศนคติ ฝั งอยู ่ ในพฤติ กรรมที ่ แสดงออกมา ในขณะที ่ กลุ ่ มอื ่ น เช่ น ฟาโซลด์ (Fasold, 1984) (Lambert et al, 1960 (Connelly & Clandinin, 1990) ทว่ าการวิ จั ยโดยการใช้ เรื ่ องเล่ าถึ งแม้ ว่ าเป็ นวิ ธี การเก็ บข้ อมู ลที ่ ใช้ อย่ างแพร่ หลายแต่ นิ ยามที ่ มี ความเป็ นสากลรวมถึ งรู ปแบบ ในการสร้ างเครื ่ องมื อในการเก็ บข้ อมู ลกลั บไม่ มี แบบแผนที ่ เป็ นฉั นทามติ (Lieblich, Tuval-Mashiach, & Zilber, 1998) Ianos et al, 2019;Lawson & Sachdev, 2000;Liu, 2019)…”
unclassified